Immune to death: humanity and human remains in the context of a research facility. (2nd April 2016) - Tradii, Laura
Abstract: This paper is based on data from fieldwork conducted in the EURAC – Institute for Mummies and the Iceman (Bozen, Italy). I observed the way in which the researchers related themselves to the object of their study: ancient human remains and through the analysis of the researchers' relationship to such remains, I argue that, contrary to what is generally stated in archaeological literature, human remains were not considered emotionally charged materials to which respect was owed in virtue of their former humanity. In particular, I will show how, in the context of the research facility in which I conducted my observations, human remains were removed from any association with the concept of death as such, for ancient skeletons and mummies were not understood to be conventional 'dead'. My work ultimately constitutes an attempt to challenge the human/non-human dichotomy by arguing that the entity, which is brought into being through bioanthropological analysis, eludes canonical categorisations.